Redundancy and Molecular Evolution: The Rapid Induction of Bone Formation by the Mammalian Transforming Growth Factor-β3 Isoform - Ripamonti, Ugo; Duarte, Raquel; Parak, Ruqayya; Dickens, Caroline; Dix-Peek, Therese; Klar, Roland M. (Frontiers in Physiology, 2016)
The soluble osteogenic molecular signals of the transforming growth factor-β (TGF-β) supergene family are the molecular bases of the induction of bone formation and postnatal bone tissue morphogenesis with translation into clinical contexts. The mammalian TGF-β3 isoform, a pleiotropic member of the family, controls a vast array of biological processes including the induction of bone formation. Recombinant hTGF-β3 induces substantial bone formation when implanted with either collagenous bone matrices or coral-derived macroporous bioreactors in the rectus abdominis muscle of the non-human primate Papio ursinus. In marked contrast, the three mammalian TGF-βs do not initiate the induction of bone formation in rodents and lagomorphs. The induction of bone by hTGF-β3/preloaded bioreactors is orchestrated by inducing fibrin-fibronectin rings that structurally organize tissue patterning and morphogenesis within the macroporous spaces. Induced advancing extracellular matrix rings provide the structural anchorage for hyper chromatic cells, interpreted as differentiating osteoblasts re-programmed by hTGF-β3 from invading myoblastic and/or pericytic differentiated cells. Runx2 and Osteocalcin expression are significantly up-regulated correlating to multiple invading cells differentiating into the osteoblastic phenotype. Bioreactors pre-loaded with recombinant human Noggin (hNoggin), a BMPs antagonist, show down-regulation of BMP-2 and other profiled osteogenic proteins’ genes resulting in minimal bone formation. Coral-derived macroporous constructs preloaded with binary applications of hTGF-β3 and hNoggin also show down-regulation of BMP-2 with the induction of limited bone formation. The induction of bone formation by hTGF-β3 is via the BMPs pathway and it is thus blocked by hNoggin. Our systematic studies in Papio ursinus with translational hTGF-β3 in large cranio-mandibulo-facial defects in humans are now requesting the re-evaluation of “Bone: formation by autoinduction” in primate models including humans.